DETERMINAN KEJADIAN DISMENORE PADA REMAJA PUTRI BERDASARKAN STATUS GIZI, IMT, KADAR HEMOGLOBIN, DAN USIA MENARCHE - Amaliyah, Nikko Izza; Fauzi, Ahmad Kholid; Munir, Zainal (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Dysmenorrhea is one of the most common menstrual disorders experienced by adolescent girls and may negatively affect daily activities, academic performance, and quality of life. Several biological factors, including nutritional status, body mass index (BMI), hemoglobin levels, and age at menarche, are considered to contribute to the occurrence of dysmenorrhea. Objective: This study aimed to analyze the relationship between nutritional status, BMI, hemoglobin levels, and age at menarche with the incidence of dysmenorrhea among adolescent girls. Methods: This study used a quantitative analytic correlational design with a cross-sectional approach. A total of 133 adolescent girls were selected using purposive sampling. Data were collected through measurements of nutritional status and BMI, hemoglobin examination using the Easy Touch GCHb device, and dysmenorrhea questionnaires. Data analysis was performed using the Chi-Square test and contingency coefficient. Results: The findings showed significant relationships between nutritional status (p = 0.000), BMI (p = 0.000), hemoglobin levels (p = 0.001), and age at menarche (p = 0.000) with the incidence of dysmenorrhea. Conclusion: Nutritional status, BMI, hemoglobin levels, and age at menarche are significantly associated with dysmenorrhea in adolescent girls. These findings indicate that biological and reproductive factors contribute to menstrual pain and may serve as a basis for preventive and promotive health interventions among adolescents.